2021
DOI: 10.9734/ijecc/2021/v11i830463
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management in Underutilized Vegetable Crop Ivy Gourd [Coccinia grandis (L.) Voigt]

Abstract: Background: Ivy gourd is the most nutritious and healthy vegetable among the underutilized vegetable crops. To increase the production effective nutrient management is key tool. Methods: The experiment on growth and yield improvement in ivy gourd through integrated nutrient management was conducted in a randomised block design with three replications at Regional Horticulture Research Station in ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Patel et al, [16] reported that "application of 50% RDF + Bio-compost had a beneficial effect on growth parameters like minimum days to flowering and fruit harvest, maximum dry biomass of shoot and dry biomass of root with near to neutral fruit pH. Maximum length of fruit, diameter of fruit, weight of fruit, maximum fruit yield per plant, highest fruit yield, maximum leaf nutrient content and soil nutrient status were also noted in 50% recommended dose of fertilizer + Bio-compost as compared to other treatment in ivy gourd".…”
Section: Ivy Gourdmentioning
confidence: 99%
“…Patel et al, [16] reported that "application of 50% RDF + Bio-compost had a beneficial effect on growth parameters like minimum days to flowering and fruit harvest, maximum dry biomass of shoot and dry biomass of root with near to neutral fruit pH. Maximum length of fruit, diameter of fruit, weight of fruit, maximum fruit yield per plant, highest fruit yield, maximum leaf nutrient content and soil nutrient status were also noted in 50% recommended dose of fertilizer + Bio-compost as compared to other treatment in ivy gourd".…”
Section: Ivy Gourdmentioning
confidence: 99%